The Analysis of Profitability Financial Ratios at Company Engaged in Property Development and Management - Parlina*, Nurhana Dhea; Maiyaliza, Maiyaliza (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
This study aims to determine and analyze the performance of a company using profitability financial ratios in companies engaged in the development and management of public property for the 2016-2020 period. The method used is descriptive statistical analysis because it is a sample description and does not intend to make conclusions. The results of the analysis of company performance using a ratio show that the Profitability Ratio shows results that are very far from standard and have poor performance using Net profit margin, Return on assets, Gross Profit Margin, Return on Investment, Return on Net Worth, and Operating Margin (OPM). Analysis of the profitability ratios shows that the company's performance tends to be poor because the resulting ratio value is below the industry average for two years and reduced profits in 2019. Keywords: NPM; GPM; ROI; RNW; OPM Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis kinerja sebuah perusahaan dengan menggunakan rasio keuangan profitabilitas pada Perusahaan bergerak di bidang pengembangan dan pengelolaan property Tbk Periode 2016-2020. Metode yang digunakan analisis statistik deskripsi karena merupakan penggambaran sampel dan tidak berniatan untuk membuat kesimpulan. Hasil analisis kinerja perusahaan dengan menggunakan sebuah rasio menunjukan Rasio Profitabilitas menunjukkan hasil yang sangat jauh dari standar dan memiliki kinerja yang kurang baik dengan menggunakan Net profit margin, Return on asset, Gross Profit Margin, Return on Investment, Rerurn on Net Worth, dan Operating Margin (OPM). Analisis rasio profitabilitas menunjukan kinerja perusahaan cenderung kurang baik karena nilai rasio yang dihasilkan dibawah rata-rata industri selama dua tahun dan berkurang keuntungan di tahun 2019. Kata Kunci: NPM; GPM; ROI; RNW; OPM